PENJADWALAN PREVENTIVE MAINTENANCE MESIN B.FLUTE PADA PT AMW - Abbas, Bahtiar S.; Steven, Edi; Christian, Harry; Sumanto, Tedy (Industrial and Systems Engineering Assessment Journal (INASEA), 2009)
PT Adina Multi Wahana has a lot of machine used in the production process therefore the maintenance process must be well scheduled and does not hinder or obstruct the existing production process schedule. The current frequency of machine breakdown is quite high and the repair time is quite high. Focus of this research is to decrease machine breakdown in order not to hinder the production process and impede the production schedule. Therefore it is recommended to implement preventive maintenance scheduling using the Age Replacement method in the company. Component replacement schedule is conducted based on 3 replacement time scenarios, namely: optimal time scenario, 60 hours replacement scenario, and 120 hours replacement scenario. The calculated results show that the monthly expenses will amount to Rp 87,554,392.60 for optimal time scenario, Rp 91,637,427.45 for 60 hours replacement scenario, and Rp 75,294,381.50 for 120 hours replacement scenario.